Analisis Penggunaan Media Whatsapp Grup dalam Pembelajaran Matematika Siswa Kelas X SMK Negeri 1 Maros - Febriansa, Awal; Syamsuriyawati; Rahmawati (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2023)
This study aims to describe: to find out the use of WhatsApp Group media in mathematics learning for grade X students of SMK Negeri 1 Maros. This research is qualitative descriptive research. The subjects of this study were students at SMK Negeri 1 Maros. Data collection was carried out by observation, interview, and documentation methods. The results showed that the implementation of research on the Use of WhatsApp Group Media is more often used in Mathematics Learning because it makes it easier to send material and attendance on WhatsApp Group media so that there are no more students who miss learning because the teacher has sent in the form of files and links. Interaction between teachers and students is quite decent in the use of WhatsApp Group Media.